LAYANAN INFORMASI MENINGKATKAN PERCAYA DIRI SISWA DALAM MENGEMUKAKAN PENDAPAT DI MAN 3 BANJARMASIN - Mahdalena, Mahdalena (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2019)
This research is motivated by the lack of confidence of students in expressing opinions in the school environment or society. Confidence in expressing opinions makes students active in the teaching and learning process, daring to express their opinions, dare to reject something that is considered incorrect, not hesitating in attitude. By increasing students' confidence in expressing their opinions, it is expected that students can become individuals who are confident in their abilities.The method used in this study is a quantitative method using the Pre-Expansion Designs design in the form of a Pretest-Posttest group. this design to find out the results of the treatment more accurately, in this study conducted 2 observations (measurements), namely comparing the conditions before and after being treated.The results of the research obtained by the Pre-test Results of the sample showed that the average percentage of self-confidence before joining the Information Service increased students' self-confidence by 35.64% which was included in the medium category. After getting the treatment experience an increase and fall into the medium category. The post test results showed that the average percentage of self-confidence after taking treatment in the form of information services increased students' confidence in expressing opinions by 64.04%, which was included in the High category.The conclusion of this study is that there is a positive change in the form of increasing students' self-confidence after being treated with information services in expressing their opinions.